M-sign in middle cerebral artery Doppler in twin-to-twin transfusion syndrome – A retrospective cohort study - Rüegg, Ladina; Zepf, Julia; Gonser, Markus; Ochsenbein-Kölble, Nicole; Vonzun, Ladina (Ultraschall in der Medizin - European Journal of Ultrasound, 2025)
In twin-to-twin transfusion syndrome (TTTS), unbalanced vascular anastomoses lead to a net transfer of fluid from the donor to the recipient. This triggers compensatory mechanisms resulting in fetal vasoconstriction. Hemodynamic modelling has shown that the appearance of a second systolic peak P2, in addition to the main systolic peak P1, in the middle cerebral artery (MCA) Doppler waveform, thus creating a systolic M-sign, may indicate increased fetal vasoconstriction. Hence, the M-sign could be expected in twins with TTTS. The Quintero staging system has been used to stage TTTS. However, TTTS does not always develop in line with the Quintero stages and/or the criteria are not always fulfilled. This study investigates whether the M-sign could be an additional TTTS criterion indicating significant imbalance between the fetuses.38 women who underwent fetoscopic laser coagulation (FLC) for TTTS were included. The MCA Doppler waveforms were retrospectively analyzed for the presence of an M-sign. We subdivided the M-signs into 2 groups: Group A: the main systolic peak P1 dominates P2, i.e., P2/P1 <1; Group B: P2 exceeds P1: P2/P1 >1.Before FLC, an M-sign was found in 17/38 (45%) pregnancies. Both twins showed M-signs in 9 pregnancies, only the recipient in 6, and only the donor in 2. In 6 (35%) fetuses, an M-sign appeared before the Quintero criteria were fulfilled. Postoperatively, M-signs disappeared in all cases.The appearance of an M-sign could be an additional marker of cardiovascular imbalance in monochorionic-diamniotic twins with developing or already present TTTS. Postoperative M-sign disappearance may indicate fetal recovery.
Keywords: middle cerebral artery; Doppler; TTTS; twins; M-sign